The influence of service quality and customer satisfaction on use loyalty BRI Mobile Banking - Ririn Rezki Fatiha; Saharuddin Saharuddin; Suhandra Makkasau (Global Academy of Multidisciplinary Studies, 2024)
Purpose: This study investigates the effect of service quality and customer satisfaction on user loyalty in BRI Mobile Banking. Research/methodology: A quantitative method was applied with a population of BRI Mobile Banking users in Palopo City. A total of 121 respondents were selected using the rule of thumb approach. Data were collected through questionnaires and analyzed using SPSS 26, including validity, reliability, regression, t-test, F-test, and determination coefficient. Results: The findings show that both service quality and customer satisfaction significantly and positively affect user loyalty. Regression results indicate that improvements in service quality increase loyalty by 0.463, while customer satisfaction contributes 0.369. The model explains 60.1% of loyalty variation, with both variables jointly exerting a significant influence (F = 91.535, p < 0.05. Conclusions: Service quality and customer satisfaction are key determinants of user loyalty. Easy application use, reliable system performance, and positive user experience foster satisfaction, trust, and long-term commitment to BRI Mobile Banking. Limitations: The study focuses only on two variables, excluding other possible factors such as trust, perceived value, or security aspects that may influence loyalty. Contribution: This research offers practical guidance for banking institutions to strengthen loyalty by enhancing service quality and customer satisfaction. It also contributes to the literature on digital banking and customer relationship management in the context of mobile financial services.